2014
DOI: 10.11564/0-0-611
|View full text |Cite
|
Sign up to set email alerts
|

The effects of household assets inequality and conflict on population health in Sudan

Abstract: We explored the effects on health of both household asset inequality and political armed conflict in Sudan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Tetanus immunisation coverage has been found to decrease during conflict 25. In west Darfur, protection against neonatal tetanus was shown to improve with an NGO’s enhancement of maternal, newborn and child health programme; however, improvements were not uniform, as interventions did not reach those living in remote communities, or in areas experiencing continued armed conflict or a lack of security 38. Another study in Sudan found that child vaccination coverage correlated with unequal household asset distributions, with conflict states having worse outcomes than non-conflict states 39…”
Section: Discussionmentioning
confidence: 99%
“…Tetanus immunisation coverage has been found to decrease during conflict 25. In west Darfur, protection against neonatal tetanus was shown to improve with an NGO’s enhancement of maternal, newborn and child health programme; however, improvements were not uniform, as interventions did not reach those living in remote communities, or in areas experiencing continued armed conflict or a lack of security 38. Another study in Sudan found that child vaccination coverage correlated with unequal household asset distributions, with conflict states having worse outcomes than non-conflict states 39…”
Section: Discussionmentioning
confidence: 99%
“…As macro data may suffer from the problem of aggregate bias, to better identify the causal relationship between the household wealth gap and individuals’ health, many studies have examined the impact from a micro perspective. For example, Omer et al (2014) [ 55 ] showed that wealth inequality significantly negatively affects the population’s physical health. Hong et al (2006) [ 56 ] examined the effect of household wealth inequality on children’s physical development and nutritional status using multivariate logit regression based on Bangladesh Demographic Health Survey data with a sample of 5977 children born at 0–59 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature presents various arguments, based on studies from different countries, about the negative correlation between health and income inequality ( Omer et al, 2014 ; Validova, 2022 ). In the context of China, Li et al (2015) explored the relationship between family assets and liabilities and happiness.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, factors such as rising real estate prices in China ( Li and Wan, 2015 ; Wan et al, 2021 ) exacerbate wealth inequality. Moreover, health issues ( Omer et al, 2014 ) and challenges in marriage ( Coontz and Folbre, 2002 ), often developed from wealth inequality, can alter people’s behaviors and potentially harm their happiness.…”
Section: Introductionmentioning
confidence: 99%